Efficacy and safety of Yi Shen Fang granules in elderly people with MCI: study protocol for a multicentre, randomized, double-blind, parallel-group, controlled trial - Zhongwei Sha; Zhenghao Zhao; Nana Li; Shuyun Xiao; Ou Li; Jie Zhang; Zhimin Li; Jian Xu (BMC, 2023)
Abstract Background Mild cognitive impairment (MCI) is a transitional state between normal ageing and dementia. Most MCI patients will progress to dementia within 5 years; therefore, early intervention for MCI is important for delaying the occurrence and progression of dementia. Yi Shen Fang (YSF) granules are a promising traditional Chinese medicine (TCM) treatment that shows great neuroprotective potential against cognitive impairment, as evidenced in clinical and basic studies. This trial aims to systematically evaluate the efficacy and safety of YSF granules in elderly people with MCI. Methods This study is a multicentre, randomized, double-blind, parallel-group, controlled trial. Based on the results of previous clinical trials, 280 elderly patients with MCI will be randomly divided into a treatment group (n = 140) and control group (n = 140). The study will last 33 weeks, including 1 week of screening, 8 weeks of intervention, and 24 weeks of follow-up. The primary outcomes will be the changes in Montreal Cognitive Assessment (MoCA) and Memory and Executive Screening (MES) scores before and after the intervention. The secondary outcome measures will be homocysteine (HCY) levels, Functional Assessment Questionnaire (FAQ) scores and event-related potential (ERP) detection in typical cases. The TCM symptom scale is a combined measure of syndrome differentiation and treatment. During this study, the classifications and characteristics of adverse events, the times of occurrence and disappearance, the measures of treatment, their impact on the primary disease, and outcomes will be reported truthfully. Discussion This study will provide valuable clinical evidence that YSF can help to improve the cognitive function of elderly people with MCI, and the results will be disseminated via conferences and publications. Trial registration Chinese Clinical Trial Registry, ChiCTR2000036807. Registered on August 25, 2020.